Pengaruh Model Pembelajaran Attention, Relevance, Confidence and Satisfaction (ARCS) terhadap Kemampuan Berpikir Matematis berdasarkan Taksonomi Bloom Revisi - Resti Yelma Sari; Netriwati Netriwati; Fraulein Intan Sari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
Abstract Thinking mathematically is a way of thinking in accomplishing the task of mathematics both simple and complex. The things that happened in this research, learners less like math lesson, lack of patience of educator in guiding learners, and model of lesser learning that can cause low mathematical thinking ability of learners. Thinking mathematically in Bloom's taxonomy is important to improve low-level thinking to high-level thinking to solve fundamental problems to complex in mathematics. the aims of this study ie to determine think mathematically based on Bloom's taxonomy revision by using the model of learning attention, relevance, confidence, and satisfaction (ARCS) is better than using a conventional learning model. The sampling technique by purposive sampling. The validity test of the instrument using product moment formula. Reliability of test instruments using Alpha formula. The prerequisite test of variance analysis is liliefors test to know normality and Bartlett test to know homogeneity, then for hypothesis testing by t-test.